Diagnostic value of the SARC-f questionnaire and muscle strength tests for the detection of sarcopenia in patients with rheumatoid arthritis - N. V. Toroptsova; O. V. Dobrovolskaya; A. O. Efremova; O. A. Nikitinskaya (Научно-практическая ревматология)
The aim of the study was to determine the diagnostic significance of the SARC-F (A Simple Questionnaire to Rapidly Diagnose Sarcopenia) questionnaire for sarcopenia screening and tests for assessing muscle strength in patients with rheumatoid arthritis.Material and methods. The study included 87 women aged 40-75 years who completed the SARC-F screening questionnaire. All patients underwent muscle strength assessment tests - wrist dynamometry and “Rising from a chair”, as well as dual X-ray absorptiometry (DXA) to quantify muscle mass. Sensitivity, specificity, diagnostic accuracy, positive predictive value and negative predictive value were determined for the SARC-F questionnaire and muscle strength tests.Results. Significant sarcopenia was diagnosed in 20 (23%) women. The sensitivity, specificity and diagnostic accuracy of the SARC-F questionnaire was 30, 42 and 39%, respectively, of the wrist dynamometry - 95, 34 and 48%, of the “Rising from a chair” test - 50, 21 and 28%, respectively. Paired use of different combinations of tests did not lead to an improvement in diagnostic value. With all three tests, the sensitivity, specificity and diagnostic accuracy were 71, 20, and 33%, respectively.Conclusion. The SARC-F questionnaire used to screen for sarcopenia has a rather low diagnostic value for identifying patients with rheumatoid arthritis in need of further evaluation. Among muscle strength tests, hand dynamometry was found to be a highly sensitive, but insufficiently specific method, which can lead to overdiagnosis of probable sarcopenia. All this indicates the need to develop a screening method specific for rheumatoid arthritis and to improve the methods of stage I of sarcopenia diagnosis.